Meanings and motivation in education research - Baguley, Margaret M.; Findlay, Yvonne S.; Kerby, Martin C. (Routledge, Taylor & Francis Group, 2015)
"Meanings and Motivation in Education Research demonstrates the vibrant and vital connection between the researcher and their research. Research is often perceived as an entity which is seemingly produced in isolation; however, there are many important factors which are involved, and this book explores the complexities of investigating the specific areas of meaning and motivation for researchers working in the education sector. With contributions from authors drawn from the field of education in various stages of their career, the perspectives shared in this book are from a diverse range of countries including Australia, Canada, Malaysia, the United Kingdom and the United States of America. Key topics include: - personal and professional identity - narrative inquiry as method - teacher educators as researchers - conducting education research - mixed methods in educational research Foregrounding the personal experiences, interests and motivations of educational researchers Meanings and Motivation in Education Research proves important insights into current discussions in educational research including researchers' identities, the ways they conduct research and most importantly the impact institutional and personal politics have on their work. This will be a valuable text for educators, education researchers, policy-makers and practitioners across the globe"
Keywords: Erziehung; Gesellschaft; Education / Research; Education / Research / Social aspects; Education / Research / Methodology; EDUCATION / Essays; EDUCATION / Organizations & Institutions; EDUCATION / Reference; Pädagogik; Forschung